2006
DOI: 10.1021/ja060802f
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Semiconducting from Metallic Carbon Nanotubes by Selective Functionalization with Azomethine Ylides

Abstract: A mild and efficient method for the functionalization of SWNTs by cycloaddition of azomethine ylides derived from trialkylamine-N-oxides is described. Selective reaction of semiconducting carbon nanotubes was achieved by preorganizing the starting N-oxides on the nanotube surface prior to generating the reactive ylides. Separation of met-SWNTs from functionalized sem-SWNTs was successfully accomplished by inducing solubilization of sem-SWNTs in the presence of lignoceric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
70
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 14 publications
(17 reference statements)
7
70
1
Order By: Relevance
“…Metallic tubes were also reported preferentially etched away by water and methane plasma because of their higher reactivity (13,14). On the other hand, H 2 O 2 (15), azomethineylides (16), and gaseous SO 3 (17) preferentially attacked s-SWCNTs, and recently s-SWCNTs were also shown to be preferentially polycarboxylated via reductive sidewall functionalization (18). However, it has not been studied yet if confinement of metal cluster catalysts within metallic and semiconducting SWCNTs affects chemical reactions differently.…”
mentioning
confidence: 99%
“…Metallic tubes were also reported preferentially etched away by water and methane plasma because of their higher reactivity (13,14). On the other hand, H 2 O 2 (15), azomethineylides (16), and gaseous SO 3 (17) preferentially attacked s-SWCNTs, and recently s-SWCNTs were also shown to be preferentially polycarboxylated via reductive sidewall functionalization (18). However, it has not been studied yet if confinement of metal cluster catalysts within metallic and semiconducting SWCNTs affects chemical reactions differently.…”
mentioning
confidence: 99%
“…1a) This was the first demonstrated method of sorting by electronic type [59]. In this method, a surfactant-stabilized aqueous suspension of single-wall carbon nanotubes is placed onto an array of interdigitated electrodes, across Dielectrophoresis [59][60][61][62][63][64][65][66][67] Electrophoresis [58] Noncovalent adsorption RNH2 (THF) 2 + filtration [68,69]; + centrifugation [70,71] Van der Waals Extraction TOAB (H2O/EA) 3 [72] Encapsulation of metallocenes [73] Reversible cyclic peptides + centrifugation [74] Charge transfer Br2 + centrifugation [75] Electrochemical doping [76] FeCl3 [77,78] K [77,78] π stacking Porphyrins + centrifugation [79] DNA + centrifugation [80] Reversible covalent functionalization [81] Chemical reaction OsO4 + hν [82] Chemical decomposition RN + 2 (l/s) [83] H2O2 [84] H plasma [85] CH4 plasma (g) [86] HNO3 [87] O2 (g) [87] H2SO4/H2O2 [88] Physical destruction Electrical breakdown (g/s) [89,90] Notes:…”
Section: Nondestructive Sortingmentioning
confidence: 99%
“…Covalent and non-covalent chemical functionalization approaches play a fundamental role to debundle and stabilize CNTs in solution where their unique characteristics can be discerned and studied. Reagents, such as oxidants [6], diazonium salts [7][8], carbenes [9], nitronium ions [10], lithium alkynylides [11], and azomethine ylides [12], have been successfully employed for the covalent modification of CNTs. Despite this rich functionalization chemistry [13][14][15][16][17], only a few comparative studies [11,18] on the addition chemistry to CNT have been reported so far.…”
Section: Introductionmentioning
confidence: 99%